Higher fat-soluble vitamin and phosphorus intake are associated with less dental caries among children and adolescents in the United States, NHANES 2011–2018 - Khan, Durdana; Hernandez-Castro, Ixel; Larvie, Doreen Y.; Armah, Seth M.; Cardenas, Andres; Malin, Ashley J. (Frontiers in Oral Health, 2025)
IntroductionHistoric research shows that a diet rich in calcium, phosphorus, fat-soluble vitamins, and vitamin C, and low in phytates may help to prevent and arrest dental caries; however, current research on this topic is scarce. We examined associations of dietary intake of these nutrients with dental caries prevalence in the United States among youth 1–19 years old.MethodsThe study included 2,676 young children (1–5 years), 3,214 older children (6–11 years) and 3,701 adolescents (12–19 years) from the National Health and Nutrition Examination Survey (NHANES 2011–2018). Daily nutrient intake was ascertained via two 24 h recalls. We assessed the number and presence (yes/no) of decayed and/or filled teeth (DFT) among young children and decayed, missing and/or filled teeth (DMFT) among older children and adolescents. Covariate-adjusted survey-weighted negative binomial regression was used to examine associations of nutrient quartiles with DFT or DMFT scores. We examined joint associations of nutrients with the probability of caries using the probit extension of Bayesian Kernel Machine Regression.ResultsMean (SD) DFT or DMFT scores were 0.82 (2.23) for young children, 2.08 (2.81) for older children and 2.51 (3.35) for adolescents. Higher phosphorus and vitamin A intake was associated with fewer DFT among young children [incident rate ratio (IRR) = 0.52, 95% CI: 0.29–0.94, p = 0.03, and IRR = 0.60, 95% CI: 0.37–0.95, p = 0.03, respectively]. Unexpectedly, higher intake of phytates was also associated with lower DFT scores among young children (IRR = 0.37, 95% CI: 0.21–0.65, p = 0.001). Higher phosphorus and vitamin E intake was associated with fewer DMFT among older children (IRR = 0.58, 95% CI: 0.40–0.84, p = 0.003 and IRR = 0.73, 95% CI: 0.54–0.97, p = 0.03, respectively). For adolescents, higher phosphorus and vitamin K intake was associated with fewer DMFT (IRR = 0.72, 95% CI: 0.53–0.99, p < 0.05; IRR = 0.82, 95% CI: 0.68–0.97, p = 0.02, respectively). The joint effect of nutrients was also associated with lower odds of DMFT. Setting all nutrients at their 75th relative to 50th percentiles was associated with 0.87 [95% credible interval (CrI): 0.81, 0.94] and 0.92 (95% CrI: 0.85, 0.99) lower odds of DMFT in older children and adolescents, respectively. Phosphorus and vitamin K contributed most to these associations.ConclusionFat-soluble vitamins and phosphorus may have systemic dental benefits that warrant further investigation.